Delayed Visual Feedback of One’s Own Action Promotes Sense of Control for Auditory Events - Kawabe, Takahiro (Frontiers in Integrative Neuroscience, 2015)
Sense of control refers to one’s feelings to control environmental events through one’s own action. A prevailing view is that the sense of control is strong (or is not diminished) when predicted sensory signals, which are generated in motor control mechanisms, are consistent with afferent sensory signals. Such intact sense of control often leads to the misjudgment of temporal relation between timings of one’s action and its effect (so-called, intentional binding). The present study showed that the intentional binding could be enhanced by the delayed visual feedback of an agent’s action. We asked participants to press a button to produce a tone as action outcome. In some conditions, they were given the delayed visual feedback of their button press. Participants judged whether the onset of the auditory outcome was delayed from the timing of their button press. Consequently, delay detection thresholds were significantly higher when the feedback was given 0.2 and 0.4 sec delays than when no feedback was displayed to the participants. The results indicate that action agents misjudge the timing of their action (button press) in the presence of the delayed visual feedback of their action. Interestingly, delay detection thresholds were strongly correlated with the subjective magnitude of the sense of control. Thus, the sense of control is possibly determined by cross-modal processing for action-related and outcome-related sensory signals.